2004
DOI: 10.1093/humrep/deh036
|View full text |Cite
|
Sign up to set email alerts
|

The levels of C-reactive protein in women treated by IVF

Abstract: In women treated by IVF the concentrations of CRP in blood increase significantly during the first week following oocyte retrieval. Successful outcome is associated with a relative small increment in CRP on the day of embryo transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 11 publications
1
28
1
Order By: Relevance
“…The available studies present considerable differences in design, subjects and methods, reaching contradictory results [17][18][19][20]. Gonadotrophin hyperstimulation, oocyte retrieval and blastocyst-endometrium interaction (i.e., early stages of implantation) are thought to induce a temporary inflammatory state as evidenced by a rise in CRP levels and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available studies present considerable differences in design, subjects and methods, reaching contradictory results [17][18][19][20]. Gonadotrophin hyperstimulation, oocyte retrieval and blastocyst-endometrium interaction (i.e., early stages of implantation) are thought to induce a temporary inflammatory state as evidenced by a rise in CRP levels and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…These and other authors [19] speculated that the inflammatory process results from stimulation treatment and may be responsible for the molecular mechanisms leading to the various degrees of the syndrome. Almagor and colleagues [18] took serial measurements of CRP during the IVF cycle and found that the levels increased 1 week after oocyte retrieval. Pregnant women after IVF treatment were shown to have higher CRP levels than non-pregnant women at 4 weeks of gestation, suggesting that the maternal inflammatory response starts from the early stages of embryo implantation [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because severe OHSS may have some features in common with the inflammatory response (leukocytosis, circulating C-reactive protein, and interleukin increase, etc.) (23,24), an anti-inflammatory treatment may be useful for preventing the onset of OHSS or to decrease its severity. If further, more targeted trials confirm the effectiveness of ASAþPred in this context, adjuvant treatment with ASAþPred could be used to reduce the incidence of severe OHSS in high-risk patients without negatively affecting IVF outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In women undergoing IVF the concentrations of CRP in blood increase significantly during the first week following oocyte retrieval. Successful outcome is associated with a relative small increment in CRP 16 in addition to its effect on the quality and maturity degree of oocyte. Therefore FF content of CRP is believed to be related to fertilization, embryo development and implantation rate 17 .…”
Section: Correlation Of Follicular Fluid ( Crp) and (Asa) Levels And mentioning
confidence: 99%